Condensed tannins from Ficus altissima leaves: Structural, antioxidant, and antityrosinase properties. Issue 8 (August 2016) - Deng, Yi-Tao; Liang, Ge; Shi, Yan; Li, Hua-Liang; Zhang, Jing; Mao, Xiao-Mei; Fu, Qi-Rui; Peng, Wei-Xi; Chen, Qing-Xi; Shen, Dong-Yan
Graphical abstract: Highlights: The total phenolic content of Ficus altissima leaves was determined. The concentration of extractable and bound condensed tannins was measured. The structure was characterized by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Reversed-phase high-performance liquid chromatography electrospray ionization mass spectrometry was also used. Condensed tannins exhibited remarkable antioxidant and antityrosinase activity. Abstract: The total phenolic content and the concentration of extractable and bound condensed tannins of Ficus altissima leaves were determined. The antioxidant activity of crude extracts and condensed tannins of F. altissima leaves was evaluated using 2, 2-diphenyl-1-pichydrazyl (DPpH), 2, 2-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and ferric-reducing antioxidant power (FRAP) methods. The results showed that condensed tannins possessed higher free radical scavenging power. The structure of condensed tannins was characterized using high-performance liquid chromatography electrospray ionization mass spectrometry coupled with thiolysis and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. The findings showed that condensed tannins from F. altissima leaves were mixtures of procyanidins, prodelphinidins, and propelargonidins with a degree of polymerization up to 30-mer. In addition, condensed tannins effectively protected plasmid DNA against free radical damage and alleviated t -butylhydroperoxide-induced cytotoxicity on human hepatocyte LO2 cells. Condensed tannins exhibited remarkable inhibitory effects on both monophenolase and diphenolase activities of tyrosinase. The IC50 values were estimated to be 256.7 ± 0.3 and 41.3 ± 0.2 μg/mL, respectively. For the diphenolase activity, inhibition by condensed tannins was reversible and of mixed-type. Condensed tannins from leaves of F. altissima were indicated to possess significant antioxidant and antityrosinase activities, suggesting that F. altissima might be a good source of proanthocyanidins with biological activity.